Leflunomide (Arava) in early rheumatoid arthritis - R V Balabanova; D E Karateev; R YKashevarov; E L Luchihina (Научно-практическая ревматология, 2005)
Objective. To assess efficacy and safety of leflunomide in the treatment of early rheumatoid arthritis (RA). Material and methods. 30 pts with RA aged 18 to 67 years were examined. 17 pts with disease duration less than 6 months (mean 3,6±2,6 months) were included in group 1 and 13 pts with disease duration from 6 months to 3 years (mean 1,8+1,3 years) - in group 2. DAS 28, ACR criteria, patient's general health, pain, HAQ, Keitel functional test and laboratory indices were used as outcome measures. Leflunomide was administered 20 mg/day during 12 months. Results. Significant decrease of RA activity indices was achieved during 3 months in both groups. Group 1 pts showed progressive improvement during the whole period of the treatment. Group 2 pts had the most prominent decrease of activity after 6 months of the treatment. Later some of them showed tendency to deterioration of several parameters. In 10 (58,8%) pts of group I clinical remission was achieved by the 6th month. The treatment was stopped because of adverse events in 4 pts. Serious adverse events were absent. Conclusion. Leflunomide (arava) is a highly effective and well tolerated disease modifying drug for the treatment of early RA. Leflunomide was more effective in pts with disease duration less than 6 months.